Obstetrics and Gynaecology - a Surgical or Medical Specialty? Obstetrics and Gynaecology Essay Prize - Gander, Lara (Trinity Student Medical Journal, 2020)
The distinction between medical and surgical approaches to disease has been a cornerstone to medical practice since its conception, the long-standing divide between the medical and surgical specialties well established, each accompanied by their own set of strengths, stereotypes and clichés. Few medical professions are boastful of combining both qualities; ENT, ophthalmology, and obstetrics and Gynaecology are the main culprits to spring to mind. However, obstetrics and gynaecology is particularly of interest, although historically bringing together medically inclined obstetricians and surgically keen gynaecologists (Smith, 1996), the rift was still evident. In modern days, increasing complexity, advancing technology, and demographic and financial changes, have altered the balance between the two, involving increasing medical expertise in gynaecology and surgical intervention in obstetrics, with a new balance to be struck and a new art to be perfected.